Efforts to Increase Student Interest in Learning in Islamic Religious Education Subjects Through the Quantum Teaching Learning Model - Desti Minda Said; Muhammad Ridwan (AIQU: Journal Multidiscipliner of Science, 2023)
This research uses a qualitative method, namely a descriptive approach that analyzes phenomena, activities, beliefs, perspectives and thoughts of people both in the form of individuals and groups. The population in this research is 90 people and the sample taken from the population is 29 people. The procedures used in this research were observation, interviews and decommentation. The results of this research are: 1). Application of the Model Application of the Quantum Teaching learning model for class VII students of SMP Negeri 17 Buton which includes: a). introductory learning activities. b). core learning activities and. c). closing learning activities. 2). Efforts to increase students' interest in learning in Islamic religious education subjects through the Quantum Teaching learning model for class VII students at SMP Negeri 17 Buton appear to be very successful in increasing students' interest in learning and implementing the Quantum Teaching learning model. In order for the Principal to fully support Islamic Religious Education, teachers must master more learning models/methods, not only lecture methods, but also use efficient and enjoyable learning models, such as one of the Quantum Teaching learning models to help keep the learning process enjoyable and not boring and gives a more interesting feel